Adomian's decomposition method applied to systems of nonlinear algebraic equations - Kaya, D; El-Sayed, SM (Elsevier Science Inc, 2004)
In this paper an algorithm based on Adomian's decomposition method is developed to approximate the solution of systems of nonlinear algebraic equations F(X) = 0. Special cases of the system of nonlinear equations are solved using the algorithm of the decomposition method. It turns out that the convergence of this algorithm is rapid. The decomposition method has the advantage of being more concise for numerical purposes. (C) 2003 Elsevier Inc. All rights reserved.
Keywords: Adomian's decomposition method; Adomian polynomials; systems of nonlinear algebraic equations